Improving the Intellectual and Social Development of Children with Autism: Design of a Training Center for Autism - Jalalian, Hasti (Makara Journal of Technology, 2021)
Research on the relationship between the role of architecture and the psychology of children with autism, which indicates that appropriate environments for these children can have a significant effect on their healthcare process, has been recently conducted. However, statistics show that autism spectrum disorders are pervasive, and its extent in Iran has been increasing. Moreover, centers that are specifically designed for children with autism are limited, and paradigms are made without considering the mood of these children. Given the role of architecture in designing a suitable space for these children, an investigation that can identify the specific requirements of these children from the architectural perspective is necessary. This research aims to design spaces that, in addition to providing relief to children, can provide a proper platform for intellectual development, social development, and promotion of social interactions. The purpose of this study is to design a training center for children with autism under 5 years old. Most of the spaces considered in the physical program have been designed to be flexible and capable of converting into spaces for children aged 5 to 14 years. The design of the center needs to take into account the qualitative criteria to build a sense of security and attachment so that it can be a place for the development and evolution of education for children with autism and the improvement of the social relationships of these children